Development Of Innovative Instructional Media Based on Lectora for Elementary School Students - Elisa; Widyasari; La Ode Amril (Indonesian Journal of Social Research (IJSR), 2019)
This research is motivated by the problem of the lack of use of school facilities and technology-based learning media in learning activities. This study aims to develop learning media in the form of innovative learning media based on Lectora applications and determine the quality of the media based on assessments by media experts, material experts, class teachers and students. This development research uses a 4D development model that is tailored to the needs of the research so it is only carried out until the third stage, namely define, design, and development. The subject of this product was conducted to 1 media expert, 1 material expert, 1 class teacher and 30 grade IV students at SDN Harjasari 01 with analysis of the research techniques used were quantitative and qualitative. Data collection in this study was carried out by observation, interview, documentation and questionnaire. Based on the analysis of research results in the form of Lectora-based innovative learning media applications which were assessed by 1 learning media expert, 1 mathematical material expert, 1 class teacher and 30 students produced conclusions worthy of use. Analysis of the feasibility assessment by mathematicians gained an average of 4.35, indicating a very good category, evaluations by instructors of instructional media obtained an average of 4.2 aimed at good categories, then an assessment by the class teacher obtained an average of 4.8 indicating very good and learning media developed were tested on 30 students and produced an average of 113.9 showing good categories. Development research that has been done can be concluded that innovative learning media based on Lectora in Mathematics Subjects of Fractional Class IV material is feasible to be used in learning in good categories according to media experts, very good according to material experts, very good according to class teachers and good according to students.